2021
DOI: 10.21203/rs.3.rs-710686/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioreduction and Bioremoval of Hexavalent Chromium by Genetically Engineered Strains (Escherichia Coli MT2A and Escherichia Coli MT3)

Abstract: Studies on the removal of toxic metals from water by genetic engineering applications are becoming more and more diverse. Especially by the expression of cysteine and thiol rich proteins such as metallothioneins in bacterial cells, a high rate of removal of metal ions from the environment is ensured. In this study, we evaluated the removal and reduction of hexavalent chromium Cr(VI)from aqueous solutions with the recombinant strains obtained by cloning the human metallothioneinsMT2A and MT3 into Escherichia co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In our previous study, we observed that Cupriavidus necator H16 cells that we treated with cadmium (Cd) exhibited higher deformation in SEM images than cells that were not treated with Cd (Akkurt et al, 2023). In addition, changes in the structure and elemental composition of recombinant MT2A and MT3 cells after biosorption of chromium (Cr) and Cd in previously published studies confirm the findings obtained in this study (Akkurt et al, 2022;Uçkun et al, 2021). EDX results (weight percentage [%]) were shown in pie chart format in (Figure 4d,e,f).…”
Section: Sem Stem Images and Ft-ir Spectroscopysupporting
confidence: 90%
See 2 more Smart Citations
“…In our previous study, we observed that Cupriavidus necator H16 cells that we treated with cadmium (Cd) exhibited higher deformation in SEM images than cells that were not treated with Cd (Akkurt et al, 2023). In addition, changes in the structure and elemental composition of recombinant MT2A and MT3 cells after biosorption of chromium (Cr) and Cd in previously published studies confirm the findings obtained in this study (Akkurt et al, 2022;Uçkun et al, 2021). EDX results (weight percentage [%]) were shown in pie chart format in (Figure 4d,e,f).…”
Section: Sem Stem Images and Ft-ir Spectroscopysupporting
confidence: 90%
“…Gene transfer experiments were carried out as described previously (Akkurt et al, 2022). MT2A and MT3 DNA fragments and the PET21 expression vector were cut with restriction endonuclease enzymes (EcoRI and NotI).…”
Section: Preparation Of the Solutions Cultivation Conditions And Gene...mentioning
confidence: 99%
See 1 more Smart Citation